2013
DOI: 10.5897/jmpr12.800
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant properties and anti-hemolytic activity of Psidium guajava, Pandanous odorus and Rhinacanthus nasutus

Abstract: The ethanolic extracts of leaves of Psidium guajava (PG), Pandanous odorus (PO), Rhinacanthus nasutus (RN) contained polyphenolic compounds in the order of PG > RN > PO. All the extracts exhibited 2,2-diphenyl-1-picryhydrazyl (DPPH) and 2,2'-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radicals scavenging activities. PG showed a marked antioxidant effect whereas PO and RN were comparable. Interestingly, they were able to bind with ferric (Fe 3+ ) and ferrous (Fe 2+) ion and completed within 5 min of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Short‐period intake of green tea in β‐thalassemia major reduced serum levels of iron, ferritin, and malondialdehyde and increased total antioxidant capacity (Soeizi et al., 2017). Similarly, polyphenols exert iron‐induced hemolysis protective effects due to the ferrous ion chelating capacity and antioxidant ability, which includes extract from mulberry fruits, extract of lotus and Psidium guajava leaves (Ajay et al., 2018; Chonthida et al., 2013; Pangjit et al., 2016). A low dose of resveratrol (5 μM) treatment reduced ineffective erythropoiesis and upregulated scavenging enzymes.…”
Section: Polyphenols Regulate Iron For Health Functionmentioning
confidence: 99%
“…Short‐period intake of green tea in β‐thalassemia major reduced serum levels of iron, ferritin, and malondialdehyde and increased total antioxidant capacity (Soeizi et al., 2017). Similarly, polyphenols exert iron‐induced hemolysis protective effects due to the ferrous ion chelating capacity and antioxidant ability, which includes extract from mulberry fruits, extract of lotus and Psidium guajava leaves (Ajay et al., 2018; Chonthida et al., 2013; Pangjit et al., 2016). A low dose of resveratrol (5 μM) treatment reduced ineffective erythropoiesis and upregulated scavenging enzymes.…”
Section: Polyphenols Regulate Iron For Health Functionmentioning
confidence: 99%
“…The assay was carried out as described by Thephinlap et al (2013) using diclofenac as standard. Typically, varying volumes (0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 ml) of extracts (1 mg/ml) were pipetted and adjusted to 1.0 ml using isosaline.…”
Section: Anti-haemolysis Assaymentioning
confidence: 99%
“…We, therefore, hypothesized a reactive oxygen species inhibiting model ( Figure 1 ) that could explain the protective effects of Rn [ 49 ]. Many other studies have shown that Rn possesses potent antioxidant effects, with the crude leaf extract showing similar free radical scavenging properties to the standard Trolox and prevent reactive oxygen species (ROS) induced hemolysis of red blood cells [ 50 , 51 ]. Furthermore, active compounds such as RnC, RnD and RnN being potent superoxide scavengers [ 52 ].…”
Section: Rhinacanthus Nasutus and Neurodegeneramentioning
confidence: 99%